Praktik Gambling dalam Game Mobile Legends: Kajian Etika dalam Perspektif Tafsir Ayat Ahkam terhadap Mekanisme Gacha - Roihan, Ahmad; Drajat, Amroeni (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2025)
The gacha mechanism is analyzed as a contemporary form of maysir (gambling) and gharar (uncertainty) that are forbidden, as they involve spending real treasures to acquire virtual items at random with low probability. The research uses a qualitative, descriptive-analytical approach with content analysis methods and in-depth interviews with Islamic legal experts. The results of the study show that gacha not only contradicts sharia principles, but also negatively impacts the consumptive, spiritual, and socio-economic behavior of players, especially generation Z. Evaluation based on sharia maqashid reveals that gacha threatens five main goals of sharia: religion, intellect, property, descent, and honor. The implications of the research emphasize the importance of strict regulation, probability transparency, Islamic financial literacy education, and the development of a more ethical game monetization model.